Variation in diets of Philippine women over 9 months of continuous observation. - Beard, J. L.; Murray-Kolb, L. E.; Lawrence, F.; Felix, A. D.; Del Mundo, A.; Haas, J. D. (2003)
The study aimed to perform a quantitative evaluation of the traditional Philippine diet using data collected over an extended period of time and to identify seasonal variations and within-subject components of variation in nutrient intake. More than 40% of calories were derived from rice, with protein from meat and fish comprising 18% of calories. There were significant variations in macronutrient and micronutrient intakes across seasons of the year, with more rice consumed in the wet season and more fruits, eggs, milk, and beverages consumed in the dry season. The day-to-day within-subject variation in median intake was 23% for energy, 31% for protein, 42% for iron, and 138% for vitamin A. These novel data showed that traditional Filipino dietary patterns have substantial individual variation and were inadequate in certain micronutrients.
Keywords: Diet; Filipino women; Dieting